The unit group of the group algebra $\mathbb{F}_{q}(\mathbb{Z}_9\rtimes\mathbb{Z}_3)$ - Sharma, R. K.; Kumar, Yogesh; Mishra, D. C. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 512.5Let $p$ be a prime, $\mathbb{F}_q$ be a finite field with $q=p^n$ elements, and $\mathbb{Z}_9\rtimes\mathbb{Z}_3$ be the  semidirect product of the groups  $\mathbb{Z}_9 $ and $\mathbb{Z}_3$. The unit group $\mathcal{U}(\mathbb{F}_q(\mathbb{Z}_9\rtimes\mathbb{Z}_3)$ of  the group algebra  $\mathbb{F}_q(\mathbb{Z}_9\rtimes\mathbb{Z}_3)$ is  completely characterized.